Game Based Learning in Higher Education: A Multicountry Analysis - Jessica REUTER; Marta FERREIRA DIAS; Marlene AMORIM; Claudia VELOSO; Claudia FIGUEIREDO; Elisabete VIEIRA (Communications of International Proceedings, 2020)
Educational institutions in recent years have followed a dynamic process of transformation and implementation of new technologies that are marked by flexibility and innovation in teaching methods. The use of educational games in higher education has roused the interest of researchers all over the world, as it is a tool that triggers the interest of students and represents an opportunity to encourage the participation and motivation in the teaching process while developing transversal competences. This work aims to analyse the use of educational games in South America, North America, and Europe in order to compare these experiences in different contexts in higher education. Through the analysis of the available literature, it is possible to obtain an overview of the reality and development of these practices and how they are meeting the needs of scholars in the face of the great diversity of the student population around the world. It also collects examples of successful development of Game based learning (GBL) in various fields of study and in the development of transversal skills.
Keywords: Game based Learning; Educational games; Gamification; Higher Education